2020
DOI: 10.21294/1814-4861-2019-18-6-75-81
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Ex Vivo Internalization Method of Water- Soluble Anticancer Drugs in Small Intestine Using Chemiluminescence

Abstract: Аннотация Введение. Способность к всасыванию в тонкой кишке (интернализация) водорастворимых противоопухолевых цитостатиков определяет возможность их перорального применения. Экспресс-метод ex vivo, моделирующий интернализацию веществ в рамках модифицированной методики изолированного «вывернутого» отрезка тонкой кишки крысы с импульсной хемилюминесценцией, адекватен для решения поставленной задачи. Цель исследования-оценка всасывания в организм из тонкой кишки новых водорастворимых противоопухолевых цитостатик… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…l -Orn is a precursor of the polyamines (PA) putrescine, spermine, and spermidine, which show diverse regulatory effects in the body. Recently, it was shown that LO can be internalized in the gastrointestinal tract [ 15 ]. As LO cleaves aliphatic positively charged AAs and can penetrate cells, we reasoned that it might be able to affect the metabolism of AAs and derive PA in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…l -Orn is a precursor of the polyamines (PA) putrescine, spermine, and spermidine, which show diverse regulatory effects in the body. Recently, it was shown that LO can be internalized in the gastrointestinal tract [ 15 ]. As LO cleaves aliphatic positively charged AAs and can penetrate cells, we reasoned that it might be able to affect the metabolism of AAs and derive PA in the brain.…”
Section: Introductionmentioning
confidence: 99%